Encapsulation of freeze-dried propolis powder: Study of in vitro disintegration and dissolution - Wan Nurul Huda, Wan Zainal; Loganathan, Enidran; Ganesan, Thavakumara (Association of Pharmaceutical Teachers of India, 2021)
Propolis is a resinous material collected by bees from various plant sources. Propolis has been used since ancient times for medicinal purposes. In this study, the propolis extracts were dried using a freeze-drying technique to preserve its medicinal properties. The effect of different freezing temperatures on the yield and propolis powder flow ability characteristics was evaluated. The potential of propolis powder to be encapsulated in hard gelatin capsules and hard hydroxypropyl methylcellulose (HPMC) capsules were investigated. The mass uniformity, in vitro disintegration and dissolution performance of the propolis powder in hard gelatine capsules and hard HPMC capsules were determined after encapsulation. The amount of propolis powder produced after freeze-drying decreased with decreasing of freezing temperature from -50°C to -80°C. Propolis powder obtained at -80°C of freezing temperature showed excellent flow ability characteristics. The average mass of propolis powder in hard gelatine capsules and the propolis powder in hard HPMC capsules was 0.5578 ± 0.019g and 0.5559 ± 0.020 g, respectively. In vitro disintegration test showed that the propolis powder that was loaded into the hard gelatine capsules disintegrated faster than the propolis powder loaded into the hard HPMC capsules, which were 1.7 to 7.8 min and 3.7 to 8.4 min in all four media solutions. Among the dissolution media tested, 1 % SLS in water showed the highest release of flavonoid. The studies of an encapsulated form of propolis powder are recommended prior to the release of a dietary supplement or clinical trial investigational product to ensure its efficacy.